1985
DOI: 10.1177/000992288502400108
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Renal Involvement in Tuberous Sclerosis

Abstract: We describe two cases of unusual presentation of tuberous sclerosis with cystic renal involvement. A 19-month-old white male who was initially misdiagnosed as having polycystic kidney disease of "adult-type" developed petit mal seizures and small "ash-leaf" depigmented areas, raising a suspicion of tuberous sclerosis. Computerized tomography (CT) of the brain revealed periventricular calcifications, confirming the diagnosis of tuberous sclerosis. A 15 3/4-year-old black female with tuberous sclerosis showed ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Out of 45 patients who had a test for serum urea and creatinine, only four had elevated levels—three of them had cysts with or without AML lesions and one had only AML. The authors suggested that the presence of renal cysts contributed to the renal dysfunction, which was also endorsed by previous reports ( 116 , 117 ). A possible mechanism is the concomitant deletions affecting the TSC2 and PKD1 genes on chromosome 16p ( 118 ).…”
Section: Renal Impairmentsupporting
confidence: 70%
“…Out of 45 patients who had a test for serum urea and creatinine, only four had elevated levels—three of them had cysts with or without AML lesions and one had only AML. The authors suggested that the presence of renal cysts contributed to the renal dysfunction, which was also endorsed by previous reports ( 116 , 117 ). A possible mechanism is the concomitant deletions affecting the TSC2 and PKD1 genes on chromosome 16p ( 118 ).…”
Section: Renal Impairmentsupporting
confidence: 70%
“…2 The kidneys of patients with tuberous sclerosis are known to have angiomyolipomas and/or renal cysts in 40% to 80% of cases. 3,4 The infant in our case presented because of massive bilateral flank masses that were found to be massively enlarged cystic kidneys bilaterally on sonography. The work-up of the large kidneys with innumerable cysts involved careful evaluation of clinical, genetic, and radiological data.…”
Section: Discussionmentioning
confidence: 79%
“…A CT scan or an ultrasound of the abdomen is almost always sufficient to diagnose polycystic kidney disease due presence of some specific features. This also differentiates cystic renal lesions from angiomyolipomas 24. ACE inhibitors are preferred antihypertensive drugs in these patients due to their renoprotective effect.…”
Section: Discussionmentioning
confidence: 92%